Right to rest of the self-employed – de lege ferenda comments - Barwaśny, Mateusz (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The subject of this study is the issue related to the right to rest of the self-employed. The current provisions of the Constitution of the Republic of Poland of 2 April 1997 in this matter are not unambiguous and they should be reviewed. First of all, they are not in compliance with acts of international law. Secondly, they do not reflect the current socio-economic realities. In the author’s opinion, the subjective scope of the right to rest should be extended to the self-employed who meet the criteria set out in the study.